The Economics of Carbon Sequestration and Climate Change Mitigation Potential of Different Soil Management Practices - Dishant Dongre; Anisha Jendre; Lalita Kumar Mohanty; Kalyani Pradhan; RAYEES A WANI; Ram Ashish; Narinder Panotra; Shital H. Bhojani; Varsha soni; Lalit Upadhyay (Archives of Current Research International, 2025)
Soil carbon sequestration has emerged as a promising strategy for mitigating climate change. The economics of soil carbon sequestration is a critical factor in determining the feasibility and scalability of this climate change mitigation strategy. Soil carbon sequestration—the process of transferring carbon dioxide from the atmosphere into the soil through crop residues and other organic solids—represents a promising strategy that sits at the intersection of agriculture, environmental science, and economics. This review explores the economics of soil carbon sequestration and its potential role in climate change mitigation. We examine the costs and benefits of various soil management practices that enhance soil carbon storage, such as reduced tillage, cover cropping, and biochar application. The review also discusses the challenges and opportunities for scaling up soil carbon sequestration, including policy incentives, carbon markets, and monitoring and verification systems. Our analysis suggests that soil carbon sequestration can be a cost-effective climate change mitigation strategy, particularly when co-benefits such as improved soil health and increased agricultural productivity are considered. However, realizing the full potential of soil carbon sequestration will require significant investment, policy support, and stakeholder engagement. Further research is needed to refine cost estimates, develop robust monitoring and verification protocols, and better understand the long-term dynamics of soil carbon storage under different management practices and environmental conditions. Study analysis suggests that soil carbon sequestration can be a cost-effective climate change mitigation strategy, particularly when co-benefits are considered. Integrating soil carbon sequestration into broader climate change mitigation and adaptation strategies, as well as sustainable land management and development plans, will be crucial for maximizing its benefits and ensuring its long-term sustainability.